Finnish children born very preterm have good reading comprehension but weak reading fluency at age 11 years – a longitudinal cohort study - Joensuu, Eveliina; Munck, Petriina; Nyman, Anna H.; Setänen, Sirkku; Rautava, Päivi; Stolt, Suvi (Informa UK Limited, 2025)
Children born very preterm (<32 gestational weeks and/or birth weight <= 1500 g) are at elevated risk for reading difficulties. This study aimed to investigate reading fluency and reading comprehension at 11 and to analyze the associations between literacy skills at 7 and reading skills at 11 in 134 Finnish-speaking very preterm children. At 11, reading fluency and reading comprehension were evaluated. At 7, pre-reading skills, decoding, and writing were assessed. Results showed that there were more preterm children with weak skills in reading fluency compared to a normative test population. Reading comprehension was age appropriate. Additionally, 62% to 68% of the children with weak literacy skills at 7 had weak reading fluency at 11, compared to those with more advanced skills (43% to 33%, p < 0.001 to 0.026). Respectively, 30% to 50% of the children with weak literacy at 7 had weak reading comprehension at 11 compared to those with more advanced skills (13% to 17%, p < 0.001 to 0.005). Findings highlight the importance of screening reading fluency until 11 years and providing support for the continuum between literacy skills in the beginning of schooling and reading outcome at later school age.